Einfluss der Biogaserzeugung auf landwirtschaftliche Pachtpreise in Deutschland; Impact of Biogas Production on Farmland Rental Rates in Germany - Hendrik Habermann; Gunnar Breustadt (German Journal of Agricultural Economics (GJAE), 2011)
– Biogas production has received considerable attention in Germany. Especially during the last years many biogas plants have been built due to increased feed-in tariffs for electricity guaranteed by the German renewable energy law. We analyse whether the use of arable and pasture land to produce 'feed' for the biogas plants increases farmland rental rates. The analysis is based on farm-level data of newly contracted rental agreements in 2005 and 2006 collected by the national agricultural census. We apply a spatial econometric approach to estimate the determinants of rental rates which explicitly takes dependence among neighbouring rental rates into account. Agricultural biogas production, measured as the share of acreage cultivated with energy crops, increases the rental rates in Western Germany significantly, but not in Eastern Germany. The estimated annual sum of additional rental payments due to biogas production projected on the whole rented acreage in Western Germany amounts to approximately exteuro 7 - 9 m. However, for rental agreements contracted after 2006 a higher impact on rental prices is expected.
Keywords: 330; Bioenergie; Förderung erneuerbarer Energien; Landpacht; Deutschland